2015
DOI: 10.1002/iid3.76
|View full text |Cite
|
Sign up to set email alerts
|

Bee venom phospholipase A2 suppresses allergic airway inflammation in an ovalbumin‐induced asthma model through the induction of regulatory T cells

Abstract: Bee venom (BV) is one of the alternative medicines that have been widely used in the treatment of chronic inflammatory diseases. We previously demonstrated that BV induces immune tolerance by increasing the population of regulatory T cells (Tregs) in immune disorders. However, the major component and how it regulates the immune response have not been elucidated. We investigated whether bee venom phospholipase A2 (bvPLA2) exerts protective effects that are mediated via Tregs in OVA‐induced asthma model. bvPLA2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 51 publications
4
50
0
Order By: Relevance
“…In contrast, our study demonstrated that increased AHR and the Th2 type cytokine productions were diminished by intratracheal injection of bvPLA2 in the OVA-challenged mice. In addition, our previous study demonstrated that Th2 cytokines, such as IL-4, IL-5, and IL-13, were inhibited by intraperitoneal administration of bvPLA2 in the OVA-induced airway inflammation mouse model [11]. Our results suggest that bvPLA2 plays an important role in Th2 responses during sensitization.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…In contrast, our study demonstrated that increased AHR and the Th2 type cytokine productions were diminished by intratracheal injection of bvPLA2 in the OVA-challenged mice. In addition, our previous study demonstrated that Th2 cytokines, such as IL-4, IL-5, and IL-13, were inhibited by intraperitoneal administration of bvPLA2 in the OVA-induced airway inflammation mouse model [11]. Our results suggest that bvPLA2 plays an important role in Th2 responses during sensitization.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, we found that PLA2 is the active compound in bee venom capable for modulating the Treg populations, both in vitro and in vivo [9,10,11]. PLA2 from bee venom belongs to group III secreted PLA2 (sPLA2) enzymes, which play important roles in a wide range of cellular functions, including phospholipid metabolism, signal transduction, and inflammatory and immune responses [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations